2022
DOI: 10.1111/joa.13750
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional architecture of human medial gastrocnemius fascicles in vivo: Regional variation and its dependence on muscle size

Abstract: Fascicle architecture (length and pennation angle) can vary regionally within a muscle. The architectural variability in human muscles has been evaluated in vivo, but the interindividual variation and its determinants remain unclear. Considering that within-muscle nonuniform changes in pennation angle are associated with change in muscle size by chronic mechanical loading, we hypothesized that the regional variation in fascicle architecture is dependent on interindividual variation in muscle size. To test this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The fiber tracking was initiated bidirectionally at a 0.1-mm step from a seed point randomly assigned within the muscle belly segmentation and repeated until 5000 fibers were extracted. The stopping criteria of fiber tracking were as follows: fractal anisotropy <0.1 or >0.5, the angle between two consecutive steps >30°, fiber length <10 mm or fiber length >200 mm, or if the tracked fiber reached outside the MG segmentation (24,35,36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber tracking was initiated bidirectionally at a 0.1-mm step from a seed point randomly assigned within the muscle belly segmentation and repeated until 5000 fibers were extracted. The stopping criteria of fiber tracking were as follows: fractal anisotropy <0.1 or >0.5, the angle between two consecutive steps >30°, fiber length <10 mm or fiber length >200 mm, or if the tracked fiber reached outside the MG segmentation (24,35,36).…”
Section: Methodsmentioning
confidence: 99%
“…The fascicle orientation is essentially in 3D, i.e., not limited to the sagittal plane (21)(22)(23). Recently, we showed the medial gastrocnemius (MG, known as a highly pennated muscle) fascicles in humans in 3D using diffusion tensor imaging (DTI) and tractography in vivo (24). It was found that fascicles ran with angles in the coronal (parallel to the aponeurosis) as well as the sagittal plane of the muscle belly (24).…”
mentioning
confidence: 99%
“…Ultrasound is a two-dimensional imaging technique, but fascicle orientation is not limited to the sagittal plane. Using magnetic resonance imaging analysis, Takahashi et al [38] showed that GM fascicles present an angular orientation in both the coronal and sagittal plane of the muscle belly. Since fascicle rotation could occur in both planes, threedimensional gearing is expected to be larger than twodimensional gearing, and its effect on metabolic energy expenditure could be even more significant.…”
Section: Limitations and Further Considerationsmentioning
confidence: 99%
“…The extrafusal muscle fibres of the medial gastrocnemius muscle have a greater diameter in male rats than in female rats (Mierzejewska‐Krzyżowska et al, 2014). Furthermore, male rats have a larger pennation angle of the medial gastrocnemius than that of females (34.6° vs. 27.3°, respectively) (Manal et al, 2006; Takahashi et al, 2022). Additionally, Chow et al (2000) found that the length of muscle fibres was greater in male individuals than in females.…”
Section: Introductionmentioning
confidence: 99%